Assessing Changes in Household Food Consumption and Nutrition Intake in Cambodia - Pirom, Khiev; Sesokunthideth, Chrea; Chanmony, Sean (WorldFish, 2024)
Cambodia has experienced profound socio-economic changes over recent years, leading to significant shifts in food consumption patterns and nutritional status. This study provides a comprehensive analysis of these changes over the past two decades, utilizing data from the Cambodia Socio-Economic Survey (CSES). Key findings indicate declining rice consumption, increased intake of proteins and fats, and a decrease in vegetable consumption, particularly green leafy vegetables. These dietary changes raise concerns about rising public health issues, including overweight, obesity, and non-communicable diseases such as diabetes and cardiovascular conditions. The study also highlights disparities among socio-economic groups, noting that vulnerable populations, including ID-Poor and Female-Headed Households, allocate up to 50% of their income to food. This research examines both at-home and away-from-home food consumption patterns, uncovering shifts towards less healthy dietary habits. While improved economic conditions have enabled broader access to diverse food options, they also exacerbate nutritional inequalities and risks of food insecurity for low-income households.